The Motif of Nature in Early Russian Soviet Utopian and Dystopian Novels - Božić, Rafaela (Poznańskie Studia Slawistyczne, 2022)
In this paper the most important works of Russian-Soviet literary utopia and dystopia have been analysed to investigate the role of nature. In literary utopias, people and their needs are the measure of all things, and the image of a utopian future is the vision of a nature so subdued that the need to eat and sleep have been subdued as well. Yet authors, such as Chayanov, emphasise the importance of a coexistence with nature. Dystopian authors ( Platonov and Zamyatin ) see the meaning of nature symbolically. They see nature not only as an unconquerable force, but also as a force entirely impermissible to defeat and that should not be defeated: for Platonov and Zamyatin nature is the eternal source of all that is to come.